Diversity of Fish Species as Bioindicators of Water Quality in The Cikapundung River, Bandung City - Fitriyyah, Ita; Firdaus, Mohamad Yosef; Kusumorini, Astuti; Akbar, Rahmat Taufiq Mustahiq (Jurnal Biologi Tropis, 2024)
Human activity along the river impacts the aquatic environment from biotic and abiotic factors. One indicator that can reflect   the quality of the waters is fish diversity. Several studies have used fish diversity as a biological indicator to determine the quality of waters, such as lake  and river waters. The purpose of this study was to determine the diversity of fish and also to determine the quality of water in the Cikapundung River, Bandung City. The method used in this study was a survey and exploration method, which involved collecting samples at five stations using umbrella traps, cast nets, and fishing gear in the morning and evening. The fish obtained were identified using the Fish Identification Guidebook, and the number of each type was calculated. The biotic data obtained were processed using the Shannon-Weiner diversity index (H'), Evenness index (E), Margalef Abundance index (Dmg), and Simpson Dominance index (C). In contrast, the abiotic data were sent to the water quality testing institution (LPKL). The study's results identified seven species from 5 families: Cyprinus sp., Ancistrus sp., Xiphophorus sp., Barbodes sp. According to the Shannon-Weiner index, the diversity of fish species in the Cikapundung River in Bandung City is relatively moderate, with a value (H') of 1.55. The results of water quality measurements of the Cikapundung River from LPKL based on the class II water quality standards of PP RI Number 22 of 2021 show that the condition of the river is in the moderately polluted category.